2020
DOI: 10.4314/acsj.v28i1.14s
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of production, consumption and export of cashew crop in West Africa

Abstract: West Africa is a core producer of Cashew (Anacardium occidentale L.), supplying 45% of the commodity on the global market. Despite this huge share of the international market, only 10% of the commodity is processed and consumed domestically. The low rate of consumption is reflected by low investment in the cashew industry, making the crop underutilised as a food and nutrition security crop in the region. The objective of this study was to analyse the trends in production, levels of consumption and export of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
4
7
0
1
Order By: Relevance
“…The percentage wastage and level of cashew apple utilization are presented in Figure 5 . The study revealed that more than 90% of the cashew apples go to waste as reported by approximately 95% of the respondents, which is in line with the studies by Ackah and Barreto [ 22 ], Oluyole et al [ 11 ], and Kolliesuah et al [ 9 ]. There is little or very low utilization for cashew apples in Ghana according to 91.7% of the stakeholders involved in the cashew business ( Figure 6 ).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The percentage wastage and level of cashew apple utilization are presented in Figure 5 . The study revealed that more than 90% of the cashew apples go to waste as reported by approximately 95% of the respondents, which is in line with the studies by Ackah and Barreto [ 22 ], Oluyole et al [ 11 ], and Kolliesuah et al [ 9 ]. There is little or very low utilization for cashew apples in Ghana according to 91.7% of the stakeholders involved in the cashew business ( Figure 6 ).…”
Section: Resultssupporting
confidence: 89%
“…Farmers form the highest (89.1%) proportion of stakeholders in the cashew industry, followed by nut buyers (6.8%), extension officers (3.5%), and cashew apple processors (0.6%). The cashew industry in Africa has been reported to mainly consist of farmers (90%) due to limited processing and other value chain activities [ 3 , 9 – 11 ]. This is therefore not surprising that there is improvement in Ghana's share of Raw Cashew Nuts (RCN) on the global market due to high productivity from farmers, but performing poorly when it comes to cashew apple processing owning to limited processors [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations